Interventional Treatment Is an Effective Approach to Relieve Symptoms in Patients With Malignant Tracheoesophageal Fistula - Pei Huang; Jinghua Cui; Zhenbang Lie; Jing Li (Cancer Reports)
ABSTRACT Background A malignant tracheoesophageal fistula (mTEF) is a complication of primary tumor growth or the recurrence of esophageal tumors or lung carcinoma. Patients with mTEF have lower survival and quality of life than those who do not develop this complication. Esophageal cancer (EC), a common gastrointestinal malignancy, ranks among the world's leading causes of cancer‐related death. The low survival rate in patients with EC is attributed to malnutrition, repeated aspiration, and severe infection; the mean survival duration is 2–4 months after diagnosis. This study investigated the clinical characteristics of patients with EC complicated with mTEF and the efficacy of various treatment regimens. Methods This study was a retrospective analysis of the clinical data of 51 patients with EC complicated with mTEF hospitalized at Guangdong Provincial People's Hospital from February 2007 to May 2021. Patients were divided into three groups according to their treatment regimen: a traditional medical (TM) treatment group, an esophageal intervention (EI) treatment group, and an airway intervention (AI) treatment group. Results Of the 51 patients, 22 received TM treatment, 13 received AI, and 16 received EI. The overall median survival duration was 87 days (TM group, 42 days; AI group, 108 days; EI group, 104 days) and the overall mean survival duration was 130.1 days (TM group, 88.1 days; AI group, 153.5 days; EI group, 166.1 days). Cox regression analysis revealed that the treatment regimen was an independent predictive risk factor for increased survival 1 month after treatment in patients with EC complicated with mTEF, and most symptoms were relieved in the EI and AI groups. Conclusions Interventional treatment of the esophagus and airway in patients with EC complicated with mTEF is an effective approach to improve symptoms and increase short‐term survival.